SOLUTION
Let us use some known facts. Let the given differential equation be
Factorize "F(D,D')" into linear factors. Then use the following results:
Corresponding to each non-repeated factor "\\left(bD-aD'-c\\right)" , the part of C.F. is taken as
In our case,
0 STEP: We factor the expression
"\\left(D^2+3DD'+2D'^2\\right)=\\left(D^2+DD'\\right)+\\left(2DD'+2D'^2\\right)="
"=D\\left(D+D'\\right)+2D'\\left(D+D'\\right)=\\left(D+D'\\right)\\left(D+2D'\\right)"
Conclusion,
1 STEP: Let find C.F.
"(C.F.)_1=\\exp\\left(\\frac{0\\cdot x}{1}\\right)\\cdot\\varphi(1\\cdot y+(-1)x)"
"\\left\\{\\begin{array}{c}\n\\left(D+2D'\\right)z\\\\\n\\left(bD-aD'-c\\right)z\n\\end{array}\\right.\\rightarrow\n\\left\\{\\begin{array}{c}\na=-2\\\\\nb=1\\\\\nc=0\n\\end{array}\\right.\\rightarrow"
Then,
2 STEP: Let find P.I.
"=\\frac{1}{D^2}\\left(1+\\frac{D'}{D}\\right)^{-1}\\left(1+\\frac{2D'}{D}\\right)^{-1}(x+y)="
"=\\frac{1}{D^2}\\left[1-\\frac{D'}{D}+\\ldots\\right]\\left[1-\\frac{2D'}{D}+\\ldots\\right](x+y)="
"=\\frac{1}{D^2}\\left[1-\\frac{D'}{D}-\\frac{2D'}{D}+\\frac{2D'^2}{D^2}+\\ldots\\right](x+y)="
"=\\frac{1}{D^2}\\left[(x+y)-\\frac{3}{D}\\left(\\frac{\\partial}{\\partial y}(x+y)\\right)+\\frac{2}{D^2}\\left(\\frac{\\partial^2}{\\partial^2 y}(x+y)\\right)+\\ldots\\right]="
"=\\frac{1}{D^2}\\left[(x+y)-\\frac{3}{D}\\left(1\\right)+\\frac{2}{D^2}\\left(0\\right)+\\ldots\\right]="
"=\\frac{1}{D^2}\\left[(x+y)-3\\int1dx\\right]=\\frac{1}{D^2}\\left[(x+y)-3x\\right]="
"\\boxed{P.I.=\\frac{x^2y}{2}-\\frac{x^3}{3}}"
Conclusion,
ANSWER
"\\left\\{\\begin{array}{c}\nz(x,y)=\\varphi_1(y-x)+\\varphi_2(y-2x)+\\displaystyle\\frac{x^2y}{2}-\\frac{x^3}{3}\\\\[0.4cm]\nwhere\\,\\,\\,\\varphi_1\\,\\,\\,and\\,\\,\\,\\varphi_2\\,\\,\\,are\\,\\,\\,arbitrary\\,\\,\\,functions\n\\end{array}\\right."
Comments
Dear Priya, please use the panel for submitting a new question.
For abelian group, identity mapping is: (a)one-one (b)onto (C)homomorphism (d)all of the above
Leave a comment